2014
DOI: 10.1063/1.4902920
|View full text |Cite
|
Sign up to set email alerts
|

Electronic, phononic, and thermoelectric properties of graphyne sheets

Abstract: Electron, phonon, and thermoelectric transport properties of a-, b-, c-, and 6,6,12-graphyne sheets are compared and contrasted with those of graphene. a-, b-, and 6,6,12-graphynes, with direction dependent Dirac dispersions, have higher electronic transmittance than graphene. c-graphyne also attains better electrical conduction than graphene except at its band gap. Vibrationally, graphene conducts heat much more efficiently than graphynes, a behavior beyond an atomic density differences explanation. Seebeck c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 69 publications
(70 reference statements)
5
42
0
1
Order By: Relevance
“…The previous NEGF calculations assumed that graphyne and graphene have the same MFP of 775 nm, and their obtained phonon thermal conductance σ ph of graphyne is 60% lower than that of graphene. 9,[19][20][21][22][23] Our works show that the mixed sp/sp 2 bonds in graphyne sheet increase phononphonon scattering, and the calculated phonon MFP of graphyne is much shorter than that of graphene, resulting in the two orders lower thermal conductivity.…”
Section: Phonon Thermal Conductivitymentioning
confidence: 90%
See 2 more Smart Citations
“…The previous NEGF calculations assumed that graphyne and graphene have the same MFP of 775 nm, and their obtained phonon thermal conductance σ ph of graphyne is 60% lower than that of graphene. 9,[19][20][21][22][23] Our works show that the mixed sp/sp 2 bonds in graphyne sheet increase phononphonon scattering, and the calculated phonon MFP of graphyne is much shorter than that of graphene, resulting in the two orders lower thermal conductivity.…”
Section: Phonon Thermal Conductivitymentioning
confidence: 90%
“…9,[19][20][21]23 The NEGF results show a monotonously increase of phonon thermal conductance with the increasing temperature. In the NEGF method, the phonon transport are treated as ballistic transport, and the phonon-phonon interaction is neglected.…”
Section: Phonon Thermal Conductivitymentioning
confidence: 90%
See 1 more Smart Citation
“…Wang et al [14,15] have calculated the ZT values of graphyne and graphyne nanotube to be 0.157 and 0.83, respectively, by using the density functional theory (DFT) calculations combined with the non-equilibrium Green's function formalism, both of which are much higher than those of graphene and carbon nanotubes. Sevinçli et al [16] calculated the ZT values of graphyne to be 0.17 at room temperature through DFT calculations and transmission spectrum analyses. For the graphyne nanoribbon, Ouyang et al [17] and Zhou et al [18] found higher ZT values of 0.25 and 0.27, respectively, based on the DFT calculation and Green's function method.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, different graphyne structures possess diverse electrical characters, like good electrical conduction 4 and native band gap [5][6][7] . It is important since the band gap engineering is the key point in application of nano electronic device.…”
Section: Introductionmentioning
confidence: 99%